Gender differences in dreaming in childhood and adolescence: the UK Library study - Georgi, Markus; Schredl, Michael (International journal of dream research, 2012)
This study evaluates gender differences in dream recall frequency, dream sharing frequency, dream listening frequency and nightmare frequency in childhood and adolescence. The sample included 3534 children for the ages from 6 to 18 who completed a brief questionnaire distributed in libraries. We were able to show that overall girls recalled dreams more often, shared dreams more often, listened more often to dreams and reported higher nightmare frequency than boys. For dream sharing frequency and dream listening frequency gender differences increased significantly with age indicating that gender-specific dream socialization might be probable. As this effect was most prominent for adolescents of 13 years and older, one might speculate that the peer group – especially same-sex friendships play an important role in dream socialization. Dream listening is still a very young field of research and longitudinal studies are necessary to study when gender differences in dreaming emerge and whether this processes effect dream recall frequency and other dream variables in adults.
Gesehen am 06.02.2019